Gambaran Histopatologi Otak Tikus Akibat Injeksi Trimetyltin sebagai Model Penyakit Alzheimer - Yuli Purwandari Kristianingrum; Sitarina Widyarini Sitarina Widyarini; Kurniasih Kurniasih; Bambang Sutrisno Bambang Sutrisno; Charles Rangga Tabbu Charles Rangga Tabbu Charles Rangga Tabbu; Sugiyono Sugiyono (Jurnal Sain Veteriner, 2016)
Trimethyltin chloride (TMT) is an organotin compound which neurotoxic at limbus system and hippocampus in human and animal. Pathology changes that caused by the induction of TMT is a neurodegenerative disorder such as nerve cell death and cognitive impairment. This study was aimed to observe brain pathology induced by TMT with multiple doses for 14, 21 and 28 days after treatment. Twenty seven of Wistar rats, at 2 months of age with weight ranging between 200-300 grams were used and divided randomly into 3 groups (n=9). Group I were injected by trimetyiltin with a dose of 6 mg / kg, group II were injected bytrimetyltin with a dose of 8 mg / kg and group III as control without injection. Observation of brain pathology was done by euthanasia on day 14, 21 and 28 after treatment, three rats each. Cortex and hippocampus of the brainwere observed using Hematoxilin and Eosin staining (HE). All of the research procedure was done with the approval and supervision of Animal Ethics Committee LPPT UGM No. 300/KEC-LPPT/VII/2015. The observation of histopathology of the brain's neuron cells injected by trimetyltin dose of 6 mg/kg and 8 mg/kg body weight was showed increasing cell death of brain neurons in the cortex and hippocampus compared to the control group. The highest cell death was on day 14 in the hippocampus and cortex cerebral on day 21after TMT injection. The neuron cell death characterized by the shrink of brain neurons as well as colored eosinophilic cytoplasm. One way ANOVA statistical analysis showed a significant difference number of neurons cell deathbetween control and treatment groups. Based on this research, it can be concluded that the trimetyltin injection dose of 6 mg / kg and 8 mg / kg of body weight caused neuron cell death in the brain rats from fourteen day aftertreatment, especially in the hippocampus and cortex.